Looking at institutional repositories in Malaysian public universities - N.N, Edzan (Persatuan Pustakawan Malaysia, 2009)
University libraries are developing and maintaining institutional repositories as a means of managing and disseminating digital materials. In most instances, these materials are created by the staff of the university and institutional repositories serve to disseminate information on the academic activities of the university community. There is a move amongst universities worldwide to develop and maintain their own institutional repositories. The size of the collection may range from hundreds to thousands and universities in Malaysia are showing signs of interest in this area. Numerous Malaysian public universities are slowly but surely developing institutional repositories either in isolation or collectively as a consortium. This paper presents the status of institutional repositories which are hosted by Malaysian public university libraries. As at 28 October 2008, the Registry of Open Access Repositories lists seven Malaysian institutional repositories and only four of them are from university libraries. This number is extremely small when compared to the existence of 20 public universities throughout Malaysia. Findings indicate that the other libraries are at various stages of developing their institutional repositories. Some are at the initial stage of designing and developing their repositories whilst others are enriching the contents of their repositories.